2012
DOI: 10.1159/000334629
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of α<sub>2</sub>-Adrenoceptor Subtypes A and C in Glucose Homeostasis and Adrenaline-Induced Hyperglycaemia

Abstract: Background and Aims: Insulin secretion is controlled by pancreatic α2A-adrenoceptors. Mice lacking α2A-adrenoceptors (α2AAR–/– mice) show hyperinsulinaemia, reduced blood glucose levels and improved glucose tolerance. Methods: In the present study, we used α2ACAR–/–, α2CAR–/– and α2AAR–/– mice and a mouse line with adrenergic cell-specific expression of α2A-adrenoceptors (lacking these recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
(37 reference statements)
7
11
0
Order By: Relevance
“…Although further investigations are needed to extend this conclusion to other imidazolines, our results evidently challenge the broadly accepted paradigm that α 2 -antagonism has minor relevance to their glucose lowering action. While most of our experiments used compounds lacking subtype specificity beyond α 2 , the observed activity of an α 2A -specific antagonist supports extensive previous evidence that α 2A is the responsible subtype for glucose lowering [5,31,37,38]. Considering the recent identification of patient subpopulations in which a congenitally higher level of α 2A -adrenergic activation of beta cells seems to contribute to the development and pathophysiology of type 2 diabetes, it is time to critically reappraise the potential utility of specifically interacting drugs in the emerging personalised medicine that is dedicated to optimal treatment selection by means of pharmacogenomics.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although further investigations are needed to extend this conclusion to other imidazolines, our results evidently challenge the broadly accepted paradigm that α 2 -antagonism has minor relevance to their glucose lowering action. While most of our experiments used compounds lacking subtype specificity beyond α 2 , the observed activity of an α 2A -specific antagonist supports extensive previous evidence that α 2A is the responsible subtype for glucose lowering [5,31,37,38]. Considering the recent identification of patient subpopulations in which a congenitally higher level of α 2A -adrenergic activation of beta cells seems to contribute to the development and pathophysiology of type 2 diabetes, it is time to critically reappraise the potential utility of specifically interacting drugs in the emerging personalised medicine that is dedicated to optimal treatment selection by means of pharmacogenomics.…”
Section: Discussionsupporting
confidence: 84%
“…Again, similar effects of yohimbine back our conclusion that this indicates an α 2 -antagonistic mode of action. While efaroxan and yohimbine lack specificity for a particular α 2 -adrenoceptor subtype, the observed antihyperglycaemic activity of the specific antagonist BRL44408 confirms earlier reports pointing at α 2A as the receptor subtype that mediates enhanced insulin secretion and decreased blood glucose [5,31,37,38].…”
Section: Antagonism At α 2 -Adrenoceptors In Vivosupporting
confidence: 86%
“…Physical activity had very little effects on serum levels of hormones reflecting glucose homeostasis, but genotype differences in insulin and resistin levels were evident. Resistin, which is a marker of insulin insensitivity [64], was decreased in α 2A -/-mice, which fits with their improved glucose metabolism [31,32], and also provides additional support for the suggested improved insulin sensitivity of the model on HFD in this study. Leptin is associated with increased adiposity, and the activity-induced weight loss suppressed leptin levels in active, regular chow-fed animals and WD-fed WT mice as expected.…”
Section: Discussionsupporting
confidence: 80%
“…Mice lacking α 2A -ARs (α 2A -/-mice) display increased sympathoadrenal tone [30,31], hyperinsulinemia and improved glucose tolerance [31,32], but differences in body weight have not been reported between α 2A -/-and WT control mice under standard diet conditions and without stressors. However, mice are generally resistant to weight gain on standard rodent chow, and the effects of reduced α 2A -AR signalling on obesogenic insults have not been comprehensively addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Postsynaptic alpha 2 -adrenergic receptors of the pancreatic b-cells are involved in insulin regulation (Ruohonen et al, 2012) and probably play an important role in the hyperglycaemic effect of alpha 2 -adrenergic agonists. However, other authors have suggested that the effects of alpha 2 -adrenergic agonist on glycaemic response are not only due to actions mediated by alpha 2 -adrenergic receptors (Ambrisko and Hikasa, 2002;Kanda and Hikasa, 2008).…”
Section: Discussionmentioning
confidence: 99%